Factors motivating employees during COVID-19: A study of the Newspaper industry in Bangladesh - Neshi, Tania Ahmed (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.